2020
DOI: 10.1080/21642850.2020.1805322
|View full text |Cite
|
Sign up to set email alerts
|

The association of illness perceptions and God locus of health control with self-care behaviours in patients with type 2 diabetes in Saudi Arabia

Abstract: Objective: To investigate the associations between illness perceptions, God locus of health control (GLHC) beliefs, and selfcare behaviours in Saudi patients with type 2 diabetes (T2D). Design: A cross-sectional study was conducted with 115 adults with T2D in a Saudi Arabian diabetes clinic. Illness perceptions, GLHC beliefs, and self-care behaviours were assessed using the Arabic versions of the Brief Illness Perception Questionnaire, God Locus of Health Control, and Summary of Diabetes Self-Care Activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 68 publications
(123 reference statements)
0
11
0
1
Order By: Relevance
“…A review previously noted that illness perception research in diabetes and other conditions has often omitted the B-IPQ item on causal beliefs [ 5 ]. Previous cross-sectional research has shown that causal beliefs are related to adherence to self-care behaviors [ 25 , 33 ]. In one prospective study, believing one’s actions in the past had caused their diabetes (personal responsibility for causing diabetes) was associated with lower HbA1c four months later in older adults, more in females than males; however, this study did not control for baseline HbA1c [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review previously noted that illness perception research in diabetes and other conditions has often omitted the B-IPQ item on causal beliefs [ 5 ]. Previous cross-sectional research has shown that causal beliefs are related to adherence to self-care behaviors [ 25 , 33 ]. In one prospective study, believing one’s actions in the past had caused their diabetes (personal responsibility for causing diabetes) was associated with lower HbA1c four months later in older adults, more in females than males; however, this study did not control for baseline HbA1c [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perceiving treatment as effective [ 21 , 22 ] and perceiving diabetes as a chronic condition [ 23 ] were associated with more frequent SMBG. Other studies, however, did not find these associations [ 12 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 85%
“…People with a stronger sense of divine control believe that God has decided what their life shall be and depend on God for help and guidance. Although numerous studies have examined the effects of divine control—and related concepts that are both general (God control, involved God, God-mediated control, and locus of God control) and specific (God locus of health control, health God control, and spiritual health locus of control)—on various health-related outcomes (Alyami et al, 2020 ; Holt et al, 2003 ; Krause & Rainville, 2022 ; Krause et al, 2017 ; Upenieks & Schieman, 2021 ; Upenieks et al, 2022 ; Wallston et al, 1999 ; Welton et al, 1996 ), little is known about smoking behavior. In fact, we could find only three relevant studies of smoking behavior (Holt et al, 2015 ; Karvinen & Carr, 2014 ; Kendler et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite limited empirical evidence with respect to smoking, divine control remains theoretically viable in the sense that these kinds of beliefs may promote or discourage healthier lifestyles or be entirely inconsequential for health behavior. While some studies show that general measures of divine control are associated with healthier behaviors (e.g., lower levels of alcohol consumption) and generally healthy lifestyles (Krause & Rainville, 2022 ; Welton et al, 1996 ), others show less healthy behavior (e.g., less exercise) or no associations with specific health behaviors (e.g., diet and sleep quality) and general health lifestyles (Alyami et al, 2020 ; Krause et al, 2017 ). Research involving more specific measures of divine health control are similarly mixed, showing healthier behavior, riskier behavior, or no association with health behavior (Alyami et al, 2020 ; Holt et al, 2003 , 2015 ; Karvinen & Carr, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that individuals’ illness perceptions are related to health outcomes across a number of chronic conditions 1,2 . In diabetes, illness perceptions have been associated with adherence to self‐care behaviours, 3 glycaemic control as assessed by glycated haemoglobin (HbA 1c ), 4,5 clinic attendance, 6 quality of life, 7 depression, anxiety 8 and mortality 9 …”
Section: Introductionmentioning
confidence: 99%